مسقطات نفقة الزوجة: دراسة فقهية مقارنة - الأهدل، فاطمة بنت قاسم بن محمد (جامعة الأزهر - كلية اصول الدين والدعوة باسيوط, 2018)
الحمد لله رب العالمين حمداً كثيراً طيباً مباركاً فيه، والصلاة والسلام على خير الأنام .. وبعد اشتمل هذا البحث على مبحثين: المبحث الأول: تعريف نفقة الزوجة، ومسقطاتها، ومشروعية النفقة، وفيه خمسة فروع وهي كالآتي: المطلب الأول: تعريف النفقة لغة. المطلب الثاني: تعريف النفقة شرعاً. المطلب الثالث: المقصود بنفقة الزوجة. المطلب الرابع: المقصود بمسقطات نفقة الزوجة. المطلب الخامس: مشروعية نفقة الزوجة. المبحث الثاني: مسقطات نفقة الزوجة، وفيه ثلاثة فروع وهي كالآتي: المطلب الأول: سقوط النفقة باختيار الزوجة، وفيه ست صور وهي: 1. امتناح الزوجة عن فراش زوجها. 2. خروج الزوجة من منزل زوجها بغير إذنه. 3. تطوع الزوجة من غير إذن زوجها. 4. منع الزوجة نفسها بالسفر. 5. منع الزوجة نفسها بالعبادة. 6. عمل الزوجة. المطلب الثاني: سقوط النفقة بغير اختيار الزوجة، وهي عدة أمور ومنها: أ‌- حبس الزوجة، ويشمل (الحبس قبل الدخول أو بعد الدخول). ب‌- مرض الزوجة، ويشمل (المرض قبل الدخول أو بعد الدخول). - المطلب الثالث: سقوط النفقة بما يكون من الزوجين معاً، وهي عدة أسباب منها: السبب الأول: اختلاف الدين. السبب الثاني: فساد النكاح. السبب الثالث: موت أحد الزوجين. ثم الخاتمة، وقائمة المصادر والمراجع. لقد تبين من خلال البحث وضوح وسمو الشريعة الإسلامية، وإحاطتها بكل الجوانب الحياتية للمسلم، والله تعالى أعلى وأعلم وصلى الله وسلم وبارك على نبينا محمد وعلى آله وصحبه ومن تبعهم بإحسان إلى يوم الدين آمين.
Praise be to Allah, the Lord of the Worlds is a good, blessed, blessed, and peace and blessings be upon the best of the eyes. This research includes two sections: • The first topic: definition of the wife's maintenance, and its residences, and the legitimacy of maintenance, and has five branches are as follows: First requirement: Definition of alimony. The second requirement is the definition of alimony. The third requirement is the maintenance of the wife. Fourth requirement: It is intended to cut the wife's expenses. The fifth requirement: the legitimacy of the maintenance of the wife. • The second topic: the expenses of the wife, and has three branches are as follows: The first requirement: the fall of alimony by choosing a wife, and there are six pictures: 1. The wife abstains from her husband's bed. 2. The wife leaves her husband's house without his permission. 3. Volunteering the wife without her husband's permission. 4. Preventing the wife herself from traveling. 5. The wife herself is forbidden to worship. 6. The wife's work. Requirement II: the fall of alimony without choosing a wife, which are several things, including: A - The imprisonment of the wife, including (imprisonment before entry or after entry). B - wife's illness, including (illness before entry or after entry). Third requirement: the fall of alimony, including the spouses together, which are several reasons, including: The first reason: the difference of religion. The second reason is the corruption of marriage. The third reason: the death of one of the spouses. Then the conclusion, list of sources and references It has been shown through the research clarity and the height of Islamic law, and surrounded by all aspects of the life of the Muslim, and God is higher and I know, peace and blessings of God and bless our Prophet Muhammad and his family and companions and those who followed them with charity to the Day of Faith Amen
Keywords: الشريعة الإسلامية -- الأحكام الفقهية -- النفقة الزوجية -- حقوق المرأة